Characteristics of the course of inflammatory bowel diseases among the residents of the Kabardino-Balkarian Republic - R. Kh. Kazhaeva; P. S. Akhmedova; R. M. Aramisova; Z. A. Kambachokova; D. Kh. Kushkhova; Z. M. Nartokova; D. E. Osmanova; S. A. Teppeeva; A. Yu. Toguzaeva; K. A. Thazaplizhev; A. A. Gukova; I. A. Kalmykov (Антибиотики и Химиотерапия)
Background. Inflammatory bowel diseases (IBD) (ulcerative colitis and Crohn's disease) are an unresolved problem in gastroenterology due to increasing incidence, progressive course, severe complications, and expensive treatment.The aim of the study was to analyze data on patients with IBD in the Kabardino-Balkarian Republic (KBR), including clinical and demographic characteristics, frequency of use of different classes of medications, and response to treatment.Material and methods. An analysis of the socio-demographic and clinical characteristics of patients with IBD who were treated in gastroenterological hospitals for the period of 2020–2022 was carried out. The analysis included data from 143 patients with ulcerative colitis and Crohn's disease.Results. Analysis of gender characteristics of the prevalence of IBD over time showed an increase in the proportion of female patients. During the study period, there was a tendency for the incidence of IBD to increase in younger age groups (20–29 and 30–39 years old). Moreover, CD was more common in young age groups than UC. IBD onset peaked between ages 20–29 years, with a slight downward trend. There was a high frequency of severe and moderate forms of IBD (78.8%) in the KBR due, in the authors’ opinion, to late diagnosis and not to the characteristics of the patient population. Extraintestinal manifestations were recorded in 37.5%, i. e. more than according to statistical data for the Russian Federation. The vast majority of patients with UC (84.8%) and CD (42.9%) received therapy with oral 5-aminosalicylic acid. Glucocorticoids were used in the treatment of 69.7% of patients with UC and 39.0% of patients with CD. 16.7% of patients with UC and 24.7% of patients with CD received immunosuppressants. In the first 2 years of the study, GEBDs were prescribed to a small number of IBD patients. GEBDs were more often used in the treatment of CD, with Infliximab being the most frequently used drug. The results of the study indicate that over the 3 years of the study, the treatment of patients became more consistent with the recommended approaches.Conclusion. The study of regional features of the course and treatment of IBD will help improve the quality and efficiency of medical care for patients both at the inpatient and outpatient stages. Creation of a regional registry of patients with IBD in the KBR will be the first step to improving the situation.